Enzyme lrnmtmoassay Technique for the Determination ofHormones inHumanSemm - Alwaan Jassim, Ayub; Hassan Kharnoob, Hussian (Tikrit Journal of Pharmaceutical Sciences, 2023)
Enzyme Linked Immunosorbant Assay (ELISA) is two immunological steps sandwich type assay. In the first step the hormone is captured by a monoclonal antibody bound to the wells of a micrometer plate. In the second step a biotinylated monoclonal antibody is added with streptavidin -peroxidase conjugate. The biotinylated antibody binds to the solid phase antibody complex and, in turn, binds the conjugate. After incubation, the wells are washed and the antigen complex bound to the well detected by addition of chromogenic substrate. The intensity of the coloration is proportional to the hormone concentration in the sample. ELISA technique for quantitative determination of Tri-iodothyroxine (13). Tetra-iodothyroxine (Ty). thyroid Stimulating Hormone (ISH). prolactin (Prol). Luteinizing hormone (111), Follicle Stimulating Hormone (FSH) and (Testo.) concentration was used. In present work the minimum detectable centrations (MDC) of | ones by this technique were estimated to be: The study was conducted in Al-Khadmia Teaching Hospital from November 2006 to June 2007 and aimed recovery, precision. accuracy and minimum detection limit of analytical technique ELISA for the determination of hormones in (35) samples of human serum.